Once a mouse ... A fable cut in wood - Brown, Marcia; Brown, Marcia (New York, Scribner, 1961)
As it changes from mouse, to cat, to dog, to tiger, a hermit s pet also becomes increasingly vain.
At head of title: From ancient India.
Keywords: Fables; Folklore -- India